The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1074/jbc.m113.506535
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 Transcription Factor Abrogates Smad4 Transcription Factor-mediated Fascin Overexpression, Invadopodium Formation, and Breast Cancer Cell Invasion

Abstract: Background: Fascin is a pro-metastasis actin bundling protein overexpressed in basal-like breast cancer. Results: GATA3 abrogates TGF␤ and Smad4-mediated fascin overexpression by abolishing the binding of Smad4 to fascin promoter. Conclusion: GATA3 is a novel suppressor of the canonical TGF␤-Smad signaling pathway. Significance: These findings provide mechanistic insight into how TGF␤-mediated invasion and metastasis are differentially regulated in different subgroups of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 44 publications
(57 reference statements)
0
42
0
Order By: Relevance
“…Our data further suggested that fascin overexpression increased MMP-2 expression through PKC-ERK signaling, which may at least partially account for the elevated invasiveness in fascin-overexpressing PDAC cells. It is also worth noting that fascin has been implicated in invadopodium formation in melanoma and breast cancer (39)(40)(41). It remains to be determined whether fascin-mediated invadopodia formation is involved in PDAC invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our data further suggested that fascin overexpression increased MMP-2 expression through PKC-ERK signaling, which may at least partially account for the elevated invasiveness in fascin-overexpressing PDAC cells. It is also worth noting that fascin has been implicated in invadopodium formation in melanoma and breast cancer (39)(40)(41). It remains to be determined whether fascin-mediated invadopodia formation is involved in PDAC invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fascin, as a prometastasis actin bundling protein, is a predictor of relatively worse prognosis in breast cancer [14] . On the basis of in vitro experimental results [9] , we hypothesised that GATA3 expression would reduce Smad4 expression and thereby also inhibit fascin expression in human breast cancer. Combined assessment of Smad4 and GATA3 expression provides more detailed information for predicting clinical outcomes in breast cancer than expression of either marker alone.…”
mentioning
confidence: 99%
“…Various proteins associated with Smad4 have been reported, but the regulatory mechanisms involving Smad4-interacting proteins remain unclear. A recent study demonstrated that GATA3 abrogated TGF-β-Smad signalling by abolishing the interactions between Smad4 and DNA elements linked to fascin function [9] . GATA3 is a zinc finger transcription factor that regulates tumour growth inhibition as well as the development and morphogenesis of the mammary glands [13] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of fascin has been reported in almost all the carcinomas (2,14,26,27), and fascin overexpression uniformly correlates with aggressive clinical course, metastatic progression, and poor prognosis (14, 28 -33). The transcriptional regulation of fascin in cancer has been extensively studied, with inflammatory cytokines, hypoxia, epithelial to mesenchymal transcription factors, and Wnt/␤-catenin pathways, among others, being implicated in the up-regulation of fascin levels in various cancers (33)(34)(35)(36)(37)(38). In contrast, little is known about the post-translational regulation of fascin other than the Ser 39 phosphorylation by PKC.…”
Section: Discussionmentioning
confidence: 99%